EFEKTIVITAS IMPLEMENTASI KEBIJAKAN PENATAUSAHAAN BARANG MILIK NEGARA: Studi pada Balai Litbangkes Banjarnegara) - Ghonimah Z Ainiyah; Siti Masiroh; Margono Margono (UNPERBA, 2021)
The problem raised in this study is the administration of goods that have not gone well because of the gap between the facts in the field and the theory used and with government regulation number 27 of 2014 concerning the management of state/regional property. This study aims to analyze the effectiveness of the implementation of state property administration policies. The location of the research was carried out at the Balai Litbang Kesehatan Banjarnegara office. This research uses qualitative research, informants are selected based on purposive sampling with 6 (six) informants and data collection through interviews, observation and attempts to design and record or take notes on the information. The results of the research that have been analyzed show that there are problems seen from 4 (four) aspects including resources, communication, disposition and bureaucratic structure that have not been maximized in managing state property, so by better understanding state property administration policies will have a significant impact on improving the administration of state property more effectively and efficiently.